The optimal portfolio of islamic stocks using the markowitz and black-litterman models - Azis, Irfani; Syazali, Muhamad; Manurung, Elise Nathalia (Universitas Islam Negeri Raden Intan Lampung, 2023)
The portfolio with the best combination of profit and risk or the investor's choice is called the optimal portfolio. The Black-Litterman and Markowitz models were used to determine the optimal portfolio during the covid-19 pandemic. Sharia stock data, that is consistent with the Jakarta Islamic Index for the 2019-2021 period, is used in this research. The stock combination of the Markowitz model is better than the Black-Litterman model. The expected value of the portfolio obtained is 0.0066, which is greater than the risk-free asset return of 0.0011 on the day of broadcast. The portfolio risk of the Markowitz model is smaller than the Black-Litterman model, which are 0.0010972 and 0.0013917, respectively. so it can be said that the Markowitz model is better than the Black-Litterman model in the formation of a Sharia stock portfolio during the covid-19 pandemic.